Rancang Bangun Sistem Informasi Pembayaran Biaya Pendidikan Pada Politeknik Lp3i Jakarta Kampus Bekasi - Dyan Yuliana; Fadly Putra Arafah (Jurnal Publikasi Teknik Informatika, 2022)
The process of paying tuition fees applied at the LP3I Jakarta Polytechnic, Bekasi Campus, currently still uses conventional methods, namely by recording on receipts and assisted by Microsoft Office Excel, so that the process of paying tuition fees runs less effectively and efficiently. From these problems, the idea emerged to create a web-based information system, which was able to manage the payment of education costs in a computerized manner. The research methods used are Library Research and Field Research, the application software used is SublimeText, XAMPP, MySQL with PHP version 7. There is one actor in this information system, namely the cashier. Cashiers can access and manage cashier data, installment data, student data, transaction data and report data. With the existence of the Education Fee Payment Information System at the LP3I Polytechnic Jakarta Bekasi Campus, it is hoped that it can facilitate the process of paying tuition fees.